Switchgrass as a bioenergy crop in the Loess Plateau, China: Potential lignocellulosic feedstock production and environmental conservation - Danielle Cooney; Hyemi Kim; Lauren Quinn; Moon-Sub Lee; Jia Guo; Shao-lin CHEN; Bing-cheng XU; D.K. Lee (Journal of Integrative Agriculture, 2017)
A large portion of the Loess Plateau of China is characterized as “marginal” with serious land degradation and desertification problems. Consequently, two policies, Grain for Green and Western Development Action were established by the Chinese government in response to the demand for ecological protection and economic development in the Loess Plateau. These policies are designed to increase forest cover, expand farmlands, and enhance soil and water conservation, while creating sustainable vegetation restoration. Perennial grasses have gained attention as bioenergy feedstocks due to their high biomass yields, low inputs, and greater ecosystem services compared to annual crops. Moreover, perennial grasses limit nutrient runoff and reduce greenhouse gas emissions and soil losses while sequestering carbon. Additionally, perennial grasses can generate economic returns for local farmers through producing bioenergy feedstock or forage on marginal lands. Here, we suggest a United States model energy crop, switchgrass (Panicum virgatum L.) as a model crop to minimize land degradation and desertification and to generate biomass for energy on the Loess Plateau.